The efforts of the Tahsin lecturer in improving students' Quran reading skills at the Syekh Abdul Halim Hasan Institute in Binjai - Sakdiah, Halimatun; Pasaribu, Syahrin (Jurnal Riset Ilmu Pendidikan, 2025)
This study aims to describe the efforts of tahsin lecturers in improving the Qur'an reading ability of students at the Institut Syekh Abdul Halim Hasan Binjai. This research uses a descriptive qualitative method with data collection techniques through in-depth interviews. The participants in this study were tahsin lecturers and students who participated in the tahsin program at the institute. The results of the study show that tahsin lecturers make several efforts to enhance students' Qur'an reading skills, such as providing intensive guidance in reading, correcting reading mistakes, and motivating students to practice more diligently. Lecturers also use individualized approaches according to the needs and abilities of each student. Furthermore, moral support and the habituation of reading the Qur'an outside the classroom also contributed to improving students' abilities. This study provides insights into the role of tahsin lecturers in teaching Qur'an reading at the higher education level.